4-(2-Azaniumylethyl)piperazin-1-ium bis(perchlorate) - Reisi, M.R.; Salga, M.S.; Khaledi, H.; Ali, Hapipah Mohd (International Union of Crystallography, 2011)
In the title compound, C6H17N32+center dot 2ClO(4)(-), the piperazine ring adopts a chair conformation with the ethylammonium fragment occupying an equatorial position. In the crystal, the dications and perchlorate anions are linked through N-H center dot center dot center dot O hydrogen bonding and weak C-H center dot center dot center dot O hydrogen bonding into a three-dimensional supramolecular network.